Issues in Tax Reform in Maine - Woodbury, Richard (Maine Policy Review, 2013)
Tax reform has been a prominent topic of public policy discussions in Maine for many years. And, while changes have been made to aspects of Maine’s tax structure over time, reforms have been piecemeal rather than comprehensive. Maine’s tax system continues to be described by critics as some combination of imbalanced, burdensome, unfair, uncompetitive, complex, archaic, and volatile. This study describes some of the features of Maine’s current tax system, and some of the approaches to reform that have been considered in recent years. The study evaluate how alternative approaches to reform might be evaluated and structured to achieve different goals, such as progressivity, growth, revenue stability and exportability. In discussing the differential impact of alternative approaches to tax reform, the distribution of taxes between residents and non-residents is among the issues highlighted in the article.